Evaluation of Bone Regeneration in Rat Calvaria Using Bone Autologous Micrografts and Xenografts: Histological and Histomorphometric Analysis - Araújo, Carlos R. G. (Materials (Basel), 2020)
The aim of this study was to investigate the effect of the use of autologous micrografts obtained by the Rigenera® Micrografting Technology and xenograft on critical size defects created in the calvaria of rats. Forty-eight rats were randomly divided into four groups for each of the two evaluation times (15 and 30 days) (n = 6). After general anesthesia, a 5-mm diameter bone defect was created in the calvaria of each animal. Each defect was filled with the following materials: blood clot, autologous bone graft, xenograft, and xenograft associated with autologous micrografts. Histomorphometric and histological analysis showed that the group that have received the Rigenera® processed autologous micrografts combined with the xenograft and the group that received autologous bone graft resulted in greater bone formation in both time points when compared with the use of the xenograft alone and blood clot.